Evaluating the Psychometric Properties of the Persian Version of the Academic Grit Scale in Iranian Students - Fatemeh Jamalinezhad; Mohammad Rostami (Iranian Journal of Educational Research)
Objective: This study aimed to examine the validity and reliability of the Persian version of the Academic Grit Scale in Iranian students using a correlational-descriptive and psychometric research design. Methods: The participants were a total of 440 male and female senior high school students in Masjed Soleyman in the academic year 2022-2023 who were selected through multi-cluster sampling. The data were collected using the Academic Grit Scale (2019), the General Grit Scale (2009), the Procrastination Assessment Scale -Students (1984), and the Multidimensional Students’ Life Satisfaction Scale (2001). The collected data were analyzed through the Pearson correlation test, Cronbach’s alpha, and factor analysis with AMOS-24 and SPSS-22 software. Results: The confirmatory factor analysis revealed the single-factor structure of the Persian version of the academic grit scale. Overall, the Persian version of the scale has acceptable and relatively strong psychometric properties in terms of content validity (CVI < 0.79 & CVR < 0.62), convergent validity with overall grit (r = 0.446; P<0.1) and life satisfaction (r=0.524; p˂0.01), divergent validity with academic procrastination (r=-0.586; p˂0.01) and internal consistency (Cronbach's alpha (α) = 0.905). Conclusions: The data from this study suggested that the Persian version of the Academic Grit Scale is an appropriate tool for evaluating academic grit in Iranian students, which can be used in research and clinical settings. The present study also provided some implications to enhance the practice of school counselors, teachers, and other professionals who try to positively influence the performance of children and adolescents.